Identification and characterization of a specific 13-miRNA expression signature during follicle activation in the zebrafish ovary†. Issue 1 (6th December 2017) - Wong, Queenie Wing-Lei; Sun, Ming-An; Lau, Shuk-Wa; Parsania, Chirag; Zhou, Shaolong; Zhong, Silin; Ge, Wei
Abstract: Ovarian folliculogenesis is always of great interest in reproductive biology. However, the molecular mechanisms that control follicle development, particularly the early phase of follicle activation or recruitment, still remain poorly understood. In an attempt to decipher the gene networks and signaling pathways involved in such transition, we conducted a transcriptomic analysis (RNA-seq) on zebrafish primary growth (PG, stage I; inactive) and previtellogenic (PV, stage II; activated) follicles. A total of 118 unique microRNAs (miRNAs) (11 downregulated and 83 upregulated during PG/PV transition) and 56711 unique messenger RNAs (mRNAs) (1839 downregulated and 7243 upregulated during PG/PV transition) were identified. Real-time quantitative polymerase chain reaction analysis confirmed differential expression of 46 miRNAs from 66 candidates (66.67%). Among which, we chose to focus on 13 miRNAs (let-7a, -7b, -7c-5p, -7d-5p, -7h, -7i; miR-21, -23a-3p, -27c-3p, -107a-3p, -125b-5p, -145–3p, and -202–5p) that exhibited significant differential expression between PG and PV follicles ( P ≤ 0.045*). With this 13-miRNA expression signature alone, PG follicles can be well differentiated from PV follicles by hierarchical clustering, suggesting their functional relevance during PG-to-PV transition. By overlaying predicted target genes and the differentially expressed mRNAs revealed by the RNA-seq analysis, especially those showing reciprocal miRNA-mRNA expression patterns, we shortlisted a panel of miRNA downstream targets for luciferase reporter validation. The reporter assay confirmed the interactions of let-7i:: atg4a ( P = 0.01*), miR-202–5p::c23h20orf24 ( P = 0.0004***), and miR-144–5p::ybx1 ( P = 0.003**), implicating these potential miRNA-mRNA gene pairs in follicle activation during folliculogenesis. Our transcriptomic data analyses suggest that miRNA-mediated post-transcriptional control may represent an important mechanism underlying follicle activation. Summary Sentence: Our transcriptomic data analyses suggest that miRNA-mediated post-transcriptional control may represent an important mechanism underlying follicle activation.